Comparative Economic Analysis of Black and Brown Commercial Layer Strains in Nigeria - Olawumi, Simeon O.; Adeoti, Adetola I. (International Journal of Poultry Science, 2009)
The present study was carried out to compare the productivity and profitability of two exotic commercial layer strains commonly raised for egg production in Nigeria. They are brown (Isa Brown) and black (Bovan Nera) feathered layer strains. Inputs such as feeds, labor and drugs as well as income generated from eggs produced including money realized from culls (spent layers) were considered for comparative economic analyses. In terms of egg production, brown feathered layers produced 326±51.3 eggs/week and black recorded 273.12±36.9 eggs/week and the difference was statistically different (p